Developing tourism associated with conserving and promoting the values of craft villages and traditional craft villages in An Giang province - Tran, Bao Nguyen (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2024)
Tourism development has always been a central and throughout objective in the socio-economic development strategy of An Giang province. In particular, developing trade village tourism is a new trend and direction, promising to bring significant economic benefits to the province. Practice shows, the problem we need to consider is how to effectively exploit the economy, both can preserve and promote the human values of trade village, traditional craft villages (referred to as craft villages). Therefore, this article aims to clarify the interaction between tourism and tourism trade village; focus on studying the reality of tourism development activities in combination with conservation and promotion of values trade village An Giang province. Thereby, proposing solutions to promote the integration process takes place widely and effectively.